Perancangan Mebel Multifungsi pada Apartemen Puncak Kertajaya - Holycia Esterano; Lintu Tulistyantoro; Grace Setiati Kattu (Intra, 2018)
Rooms that can accommodate daily activities in a multi-storey building are called apartment. The apartment has a limited space, therefore it cannot accommodate the activities of medical students who need a comfortable place to learn. Therefore, it takes a multifunctional furniture design that has high efficiency and comfort to answer user problems. The methods for this design are the following steps, empathize, define, ideate, prototype, and test. The purpose of this design is to study and understand the needs of medical student activities that spend a very long time to learn can be contained in a multifunctional furniture and produces multifunctional furniture that has the utility for leisure, study, and storing things.